Rethinking medicinal plants and plant medicines. Issue 1 (2nd January 2018) - Gibson, Diana
Abstract : Because plants are perceived as sessile and immobile, they are often represented as objects or things in current literature. In this paper, I explore variations and shifts in research and literature since 2000 that reconsider the ways that plant-related ideas, expertise and practices intersect in multiple associations related to medicinal plants. I argue that, in their relationship with humans, plants have histories, are mobile and can also bring about political and other effects. I use ethnographic material from Namibia and the Western Cape of South Africa to review medicinal plants, by focusing on human-plant relations and the incorporation of plants as non-human subjects with non-intentional agency.